Salt and blood pressure in Belgium. Issue 4 (December 1981) - Staessen, J; Fagard, R; Lijnen, P; Amery, A; Bulpitt, C; Joossens, J V
Abstract : Blood pressure, pulse rate, body weight, and height were measured on two occasions in the inhabitants of a random 10% sample of households in a Belgian village. Twenty-four-hour urinary excretion of creatinine, sodium, and potassium was also determined. In subjects over the age of 19 there was a significant correlation for both systolic and diastolic pressure with age and body weight and, in women, also with pulse rate. After adjusting for these three variables, the systolic blood pressure in men was negatively correlated with the daily urinary potassium excretion, and the diastolic blood pressure in women negatively with the urinary sodium: creatinine ratio. The present data, obtained within one society, do not support a role for dietary sodium in the distribution of blood pressure within this population. Comparison of the present results with data from other countries does not refute the salt-genetic hypothesis but suggests also that a high potassium intake may lower blood pressure.